Physical education, muscle strengthening exercise, sport participation and their associations with screen time in adolescents - Hu, Xiaoqing; Drenowatz, Clemens; Duncan, Michael; Bao, Ran; Chen, Sitong; He, Jinsheng; Tang, Yan (Frontiers in Public Health, 2023)
Backgroud/Objective: Physical activity (PA) has been suggested to reduce screen time. This study aimed to explore the associations of physical education (PE), muscle-strengthening exercise (MSE), and sport participation with screen time. Methods: A multi-cluster sampling design was used to select 13,677 school-aged adolescents that participated in the YRBS 2019 survey. Adolescents self-reported their frequency of PE attendance, MSE, sport participation and hours for screen time. Additionally, participants provided demographic information including sex, age, race, and weight status. Results: Collectively, there were beneficial associations between participating in MSE for 4 (OR = 1.31, CI: 1.02-1.68), 5 (OR = 1.65, CI: 1.31-2.08), 6 (OR = 2.23, CI: 1.47-3.36), 7 (OR = 1.62, CI: 1.30-2.01) days and video or computer game hours. Similarly, beneficial associations between participating in 1 team sport (OR = 1.23, CI: 1.06-1.42), 2 team sports (OR = 1.61, CI: 1.33-1.95), 3 or more team sports (OR = 1.45, CI: 1.16-1.83) and video or computer game hours were observed. Participating in 1 team sport (OR = 1.27, CI: 1.08-1.48), 2 teams sport (OR = 1.41, CI: 1.09-1.82), 3 or more team sport (OR = 1.40, CI: 1.03-1.90) also increased the odds for meeting guidelines for television viewing hours. Only 2 days of PE attendance (OR = 1.44, CI: 1.14-1.81) was significantly associated with video or computer game hours. Conclusion: The promotion of sports participation appears to be an important component for reducing excess screen time in adolescents. Further, MSE may have beneficial effects on time spent on the computer and playing video games.